Evaluation of Service Quality at the SGS PLN Bandung Badminton Club Based on the SERVQUAL Model - Mila Utami; Tono Haryono; Septiyan Williyanto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to assess the quality of management services at the SGS PLN Bandung Badminton Club by utilizing the SERVQUAL model, which consists of five main aspects: tangibles, reliability, responsiveness, assurance, and empathy. Using a quantitative method and a descriptive correlational design, the study objectively captures the athletes' perspectives while examining the relationships between those service dimensions. The research population includes all active athletes participating in the club's training activities, with a purposive sample of 23 respondents who have been involved in training for at least one year. The data collection instrument is a SERVQUAL questionnaire adapted for the sports context, based on the study by Cristobal Fransi and colleagues in 2010. The validity test results show that all questionnaire items are valid (r values ranging from 0.510 to 0.885 with p < 0.05) and highly reliable (Cronbach’s Alpha of 0.963). From the descriptive analysis, it can be seen that the overall quality of the club's services is quite satisfactory, with the best scores in the aspects of tangibles and empathy—which indicates that the physical facilities and attention to athletes are already quite good—while responsiveness received the lowest score, suggesting that the response to athletes' needs needs improvement. Ultimately, the club management has been running well, but responsiveness and assurance need to be strengthened to enhance athletes' satisfaction and trust.